Handbook of Labor, Human Resources and Population Economics - Zimmermann, Klaus F. (Springer, 2020)
Affirmative Action and Employment -- AI and robotics innovation: a sectoral and geographic mapping using patent data -- Attorneys as Professional Human Resources: When do Plaintiffs Prefer Contingent Fees to Hourly Fees? -- Bayesian Econometrics Methods -- Behavioral Aspects of Communication in Organizations -- Behavioral aspects of recruitment and job search -- Big Data Methods -- Bonus plans, subjective performance evaluations and career concerns -- Bounding Methods -- Brain Drain or gain -- Causality -- Causes and Consequences of Illicit Drug Epidemics -- Child labor and economic development -- Child migration -- Citizenship -- Climate Change and Migration -- Climate shocks and natural disasters -- Clustering Methods for Statistical Inference -- Conflict -- Contract labor in developing countries -- Control Functions and Selection Models -- Costs of Victimisation -- Decomposition Methods -- Design and Analysis of Experiments -- Determinants of Migration -- Diaspora economics -- Digital Platforms and the Transformations in the Division of Labour -- Digitization and the future of work: macroeconomic consequences -- Domestic and imported new technologies in developing countries: the employment impact -- Drinking and Driving -- Duration Models -- Early Life Health Shocks and Labor Market -- Economic migrant assimilation -- Economics of early marriage -- Economics of obesity -- Economics of sex work and policy considerations -- Economics of smoking -- Economics of Suicide -- Education and wage inequality -- Effects of ICT Investment on Labour Demand in OECD Countries -- Employer-Employee Data Methods -- Employment insurance and social protection -- Empowering Women over the Last Two Decades: Lessons for the Fifth Sustainable Development Goal -- Environmental pollution & labor productivity -- Ethnicity, Race and Minorities -- Fair and unfair income inequality -- Family left behind -- Feedback policies and peer effects at work -- Female genital mutilation and labor market consequences -- Fertility and Female Labor Force Participation -- Foreign remittance, poverty and economic growth -- Gender and Income Inequality -- Gender and Inequality in the Workplace: Lessons from Institutional and Marxist Perspectives -- Gender and intrahousehold issues -- Gender Gaps in Education -- Gender Identity and Sexual Orientation in Later Life -- Gender Identity Minorities and Workplace Legislation in Europe -- Gender Mainstreaming Poverty and Social Inclusion -- Gender on the labor market -- Gender Roles and Families -- Gender Stereotypes and Gender-Typed Work -- Gender Wage Gaps and Skills -- Gender, Financial Crisis and Labor Markets -- Gender, Gender Self-Perceptions, and Workplace Leadership -- Gender, Time Allocation, and Birth Controls -- Group identity, in-group favoritism, and discrimination -- Health and Wellbeing in Sexual Minority People and Economic Considerations -- Health, disability & nutrition -- Human Smuggling -- Immigrant entrepreneurs -- Inequality and Family Policy -- Inequality and Top Incomes -- Inequality Measurement: Methods and Data -- Inequality of opportunities in the labor -- Inequality of Opportunity -- Informality and labor market dualism/segmentation -- Innovation and Self-employment -- Innovation, employment and the business cycle -- Innovation, technology adoption and employment: Findings from evidence synthesis -- Integration in Global Value Chains and Employment in Europe -- Interethnic marriages -- Intergenerational occupational mobility -- Interventions on non-cognitive skills in education: Experimental evidence -- Labor Force Status of Transgender Men and Women: What we Know -- Labor market for sex workers/stigma and occupational choice -- Labor Mobility -- Labor negotiations, conflicts, and arbitration -- Language and migrant performance -- Leadership and delegation of authority -- Light, Moderate, and Heavy Drinking: Evidence from around the world -- Masculinity, Femininity and Workplace Outcomes -- Measurement Error Models -- Measuring migration -- Media Exposure, Attitudes Towards Migration and the Political Economy of Immigration -- Mediation Analysis -- Microfinance and employment -- Migrant Health -- Migrant occupational mismatch -- Migrant Wellbeing -- Migration and Aging -- Migration and culture -- Migration and Education -- Migration and Environment -- Migration and the Natives -- Migration Policy -- Morality and anti-social behavior at work -- Natural resources & oil curse -- New technologies and Routinization: How robust is the evidence for the EU? -- New technologies and the skill mismatch -- New technologies, structural change, the process of development and the labor market -- Non-cognitive skills (including ECD) and labor market outcomes -- Ordinal Variables and the Measurement of Inequality, Poverty and Welfare -- Panel Data Models -- Performance of Migrants -- Personality and success in education and on the labor market -- Policing and Crime -- Political Economy of Child Labour -- Political Economy of Minimum Wages -- Posted Workers -- Precarious Work and Gender -- Quantile Regression Methods -- Quantity and quality of work in the platform economy -- Reference points and effort -- Refugees and natives -- Refugees; forced Migration -- Regression Discontinuity Design -- Remittances -- Remittances and Economic Development in the Country of Origin -- Return and circular migration -- Risk and Prevention of Infectious Disease -- Risky Behavior and Its Consequences During Adolescence and Young Adulthood -- Robot density and employment in developed and developing countries -- Robots at work: automatable and nonautomatable jobs -- Robots, structural change and employment: future scenarios -- Selection on Observables -- Self-confidence and motivation -- Semi - and Non-Parametric Methods -- Sexual Orientation and Gender Identity in the Workplace: A Review on Employees’ Experiences -- Simultaneous Equations and Instrumental Variables Models -- Skills shortage, educational mismatch & youth unemployment -- Skill-sets for prospective careers of researchers and engineers -- Social Integration and identity -- Social Interaction Methods -- Social networks -- Social preferences, pro-sociality and social norms -- Social remittances -- Structural Models -- Sweatshop Labor -- Team decision-making -- Technological change, innovations (automation) productivity shocks/job destruction -- Technological innovations and heterogenous Labour demand using linked firm-level data -- Technology and employment: key stylized facts for the digital age -- Testing the employment and skill impact of new technologies: A survey and some methodological issues -- The Behavioral Approach to Entrepreneurship -- The Political Economy of Citizenship: Education-Occupation Mismatch and the Role of Social Networks -- The Political Economy of Effects of Mis-matched Governance on Urban Human Resource Planning -- The Political Economy of Immigration and Crime -- The Political Economy of Strikes: A Socio-economic Indicator -- Time Series Models -- Tournaments and competition -- Trans People, Transitioning, Mental Health, Life and Job Satisfaction: A Review -- Transgender Employees Transitioning and Discrimination -- Up in smoke? The market for Cannabis -- Violence and Risky Behavior in Professional Sports -- Wage policies, incentive schemes and motivation -- Wealth Inequalities -- Welfare migration -- Women's empowerment (domestic violence) and employment -- Work, aging and retirement